2004
DOI: 10.1016/j.cell.2004.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Adaptive Energy Metabolism with CNS-Linked Hyperactivity in PGC-1α Null Mice

Abstract: PGC-1alpha is a coactivator of nuclear receptors and other transcription factors that regulates several metabolic processes, including mitochondrial biogenesis and respiration, hepatic gluconeogenesis, and muscle fiber-type switching. We show here that, while hepatocytes lacking PGC-1alpha are defective in the program of hormone-stimulated gluconeogenesis, the mice have constitutively activated gluconeogenic gene expression that is completely insensitive to normal feeding controls. C/EBPbeta is elevated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

54
1,060
10
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,085 publications
(1,143 citation statements)
references
References 45 publications
54
1,060
10
5
Order By: Relevance
“…Mice The generation and phenotype of PGC-1α KO mice have been described previously (Lin et al 2004). The genotype of the offspring was assessed by determining the presence of either a wild type (WT)-or KO-specific DNA fragment after extraction of DNA from a tail piece by the phenol-chloroform/isoamyl method, amplification of fragments by PCR using specific primers and separation on an agarose gel.…”
Section: Methodsmentioning
confidence: 99%
“…Mice The generation and phenotype of PGC-1α KO mice have been described previously (Lin et al 2004). The genotype of the offspring was assessed by determining the presence of either a wild type (WT)-or KO-specific DNA fragment after extraction of DNA from a tail piece by the phenol-chloroform/isoamyl method, amplification of fragments by PCR using specific primers and separation on an agarose gel.…”
Section: Methodsmentioning
confidence: 99%
“…They increase mitochondrial energy production by inducing the expression of genes that regulate fatty acid oxidation and by increasing mitochondrial activity (Kamei et al, 2003;Lin et al, 2003;Meirhaeghe et al, 2003;St-Pierre et al, 2003). Moreover, mice lacking either PGC-1a or PGC-1b exhibit little to no effect on mitochondrial mass and respiration activity (Lin et al, 2004;Leone et al, 2005;Lelliott et al, 2006;Sonoda et al, 2007). However, RNAimediated down-regulation of PGC-1b in PGC-1a À/À preadipocyte lines additively inhibits mitochondrial respiration (Uldry et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, instead of the expected impairment, G6pc and Pepck gene expression were surprisingly elevated in the fed state to a level equivalent to that in the fasted state. This elevation of G6pc and Pepck expression was potentially caused by elevated hepatic C/ebpβ (also known as Cebpb) gene expression [8]. In contrast, in their mice, Leone et al [9] observed euglycaemia in the fasted state with no elevation of G6pc, Pepck or C/ebpβ expression in the fed state and the same induction following fasting as seen in wild-type mice.…”
Section: Introductionmentioning
confidence: 93%
“…However, these groups reported variable effects of PGC-1α deletion on hepatic gluconeogenic gene expression and fasting blood glucose levels. Lin et al [8] observed hypoglycaemia in the fasted state and reduced HGP. However, instead of the expected impairment, G6pc and Pepck gene expression were surprisingly elevated in the fed state to a level equivalent to that in the fasted state.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation